7.7 THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF USING OPEN ONLINE EDUCATIONAL RESOURCES IN A HIGHER EDUCATION INSTITUTION - Ismailov Shixnazar Rashid o‘g‘li., Kuziev Shakhzod Ulug‘bek o‘g‘li., Talipova Ozoda Xabirovna. Tashkent University of Information Technologies named after Muhammad al-Khwarizmi (Innovative technologies in construction Scientific Journal, 2024)
Ushbu maqolada axborot-kommunikatsiya texnologiyalaridan (AKT) foydalanish va axborotdan erkin foydalanishni ta'minlash, ochiq ta'lim resurslarini yaratish, rivojlantirish va rag'batlantirish dunyoning ko'plab mamlakatlarida keng tarqalganligi tasvirlangan. Shu bilan birga Ochiq ta’lim resurslari bo‘yicha Butunjahon kongressida quyidagi masalalar ko‘rib chiqildi. Global tarmoq, Ochiq ta'lim resurslari, Inson resurslarini rivojlantirish. Kalit so'zlar: Global tarmoq, axborot resurslari, Ochiq ta'lim resurslari, Inson resurslarini rivojlantirish. Аннотатция. В данной работе использование информационно-коммуникационных технологий (ИКТ) и обеспечение свободного доступа к информации, создание, развитие и продвижение открытых образовательных ресурсов описываются как широко распространенные во многих странах мира. При этом на Всемирном конгрессе по открытым образовательным ресурсам были освещены следующие вопросы. Глобальная сеть, Открытые образовательные ресурсы, Развитие человеческих ресурсов. Ключевые слова: Глобальная сеть, информационные ресурсы, открытые образовательные ресурсы, развитие человеческих ресурсов. Annotation. In this paper, the use of information and communication technologies (ICT) and the provision of free access to information, the creation, development and promotion of open educational resources are described as widespread in many countries of the world. At the same time, the following issues were covered at the World Congress on Open Educational Resources. The global network , Open Educational Resources , Human Resource Development. Keywords: The global network , the information resources, Open Educational Resources , Human Resource Development. This article discusses the difficulties that arise when learning a non-native language under interfering influence of the native language. The article analyzes phonetic, graphic and spelling, grammatical (morphological and syntactic), lexical-semantic and stylistic interference. The use of information and communication technologies (ICT) and the provision of free access to information are the main conditions for the formation of a knowledge-based society.[1] Today, the global network of the Internet is the most sought-after source of knowledge, which provides access to various information in various formats. It is no exaggeration to say that the number of websites has reached tens of millions. Among the ever-increasing variety of information resources, choosing the right educational and scientific information sources is becoming increasingly difficult for both students and educators.[2] The movement to create, develop and promote open educational resources has become widespread in many countries of the world in the last decade. Universities are increasingly revealing limitations to the use of their teaching and research resources. The creation and development of open educational resources is actively supported at the national and international levels.[3] According to him, he distinguished the following main trends: Fundamental change of roles and functions of universities; Revising the requirements for lifelong (continuous) education; Strengthen national and international quality control, accreditations and recognition of qualifications; The need to promote distance education in order to further support the full integration of ICT and meet the growing demands for the quality of Life Long Learning in higher education was emphasized. The increasing rate (pace) of technologies has created new issues that need to be solved together with higher education, government and industry, such as the acquisition of experiences, the development of a legal framework and the sharing of positive experiences. Special attention was paid to the need to ensure quality education, especially the use of open educational resources.